Impact of sleep disorders on cardiovascular diseases - Bartosz Snopkowski; Patrycja Szponarowicz; Eliasz Panek; Damian Jasłowski; Mateusz Rzeszutko; Przemysław Raczkiewicz; Dominika Panasiuk; Mateusz Skrętowicz; Tomasz Korzec; Jakub Sosnowski (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Sleep disorders are a diverse and widespread group of diseases affecting the cardiovascular system. The aim of this paper is to review the available literature and to summarize how selected sleep disorders affect the development of hypertension, ischemic heart disease and stroke. Methods and materials: Materials available in the PubMed and Google Scholar database were analyzed using the keywords “sleep disorders”; “sleep apnea”; “insomnia”; “restless legs syndrome”; “cardiovascular disease”; “hypertension”; “coronary artery disease”; “stroke " in various configurations. State of knowledge: Sleep disorders are a wide group of diseases with a diverse phenotype and pathomechanism, having a diverse impact on the condition of the cardiovascular system, leading to the development of diseases in the above system. Summary: The risk of developing hypertension, ischemic heart disease and stroke depends on the accompanying sleep disorders. Occurs with obstructive sleep apnea and sleep shortening. The correlation of restless legs syndrome to stroke is unclear. The relationship between insomnia and hypertension and stroke is not clarified. Keywords: sleep disorders, cardiovascular diseases, sleep apnea, insomnia, restless legs syndrome.